Revitalisasi Kawasan Wisata Embung Hutadaa di Kabupaten Gorontalo dengan Konsep Arsitektur Ekowisata - Mohammad Jufri Salam; Beby Sintia Dewi Banteng; Ria Selfiyani Bahrun (Jurnal Ilmu Teknik Terapan, 2026)
Gorontalo province holds significant tourism potential, but many of its sites, including Embung Hutadaa, suffer from poor facilities and a lack of proper planning, leading to a decline in their appeal. This study proposes to revitalize the Embung Hutadaa tourist area by applying an ecotourism architectural concept as a strategic solution. Through a qualitative case study and architectural analysis, the research identifies that while Embung Hutadaa possesses a beautiful natural landscape, its current condition is suboptimal. Therefore, a masterplan was developed based on three core principles: environmental conservation, education, and community participation. The proposed design includes a clear division of zones (public, semi-public, private), an eco-friendly circulation system, and supporting facilities like an education center, local MSME stalls, and conservation areas. The use of local materials such as wood and bamboo is also recommended to strengthen the architectural identity and promote sustainability. This revitalization project is expected to restore Embung Hutadaa's function as a leading and sustainable tourist destination. By revitalizing the area, it will not only boost regional tourism but also preserve the environment and provide long-term economic and social benefits for the local community.